The Influence of Halal Attractions and Memorable Experiences on Tourists' Destination Choices: An Indonesian Perspective - YASIN, Muaidy; HERMAN, Lalu Edy (Journal of Environmental Management and Tourism, 2023)
The objective of this research is to analyze the influence of the tourism brand on decision-making developments during the holidays, as well as the contribution of religious standards, hallucinations and memorable tourist experiences. Tourism, a prominent step in the brand, is gaining a lot of attention and promotion in Indonesia. The study perfect is empirically authenticated through a field survey, a questionnaire distributed to 150 people surveyed by sampling methods. The collected data was processed with the Amos 20 software using Structural Equations (SEM). The results of the study show that memorable tourist experiences affect the natural value of a person's religiosity and the decision to visit a destination, and captivation also influence tourism choices. However, neither the attractive tourist brand nor the attraction affects the religiosity of a place, and the value of religiosity does not play roles in the judgements that tourists make to visit it.